2017
DOI: 10.1098/rspb.2017.1026
|View full text |Cite
|
Sign up to set email alerts
|

Can hook-bending be let off the hook? Bending/unbending of pliant tools by cockatoos

Abstract: The spontaneous crafting of hook-tools from bendable material to lift a basket out of a vertical tube in corvids has widely been used as one of the prime examples of animal tool innovation. However, it was recently suggested that the animals' solution was hardly innovative but strongly influenced by predispositions from habitual tool use and nest building. We tested Goffin's cockatoo, which is neither a specialized tool user nor a nest builder, on a similar task set-up. Three birds individually learned to bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 28 publications
2
67
0
Order By: Relevance
“…Tool use innovations can be transmitted to naïve individuals by emulation learning and tool-using subjects are thereafter able to independently innovate tool manufacture (Auersperg et al, 2014). The birds respond flexibly, not only when choosing a tool, but also when making different tools from different materials depending on the problem at hand (Auersperg et al, 2016;Laumer et al, 2016Laumer et al, , 2017Habl & Auersperg, 2017;Auersperg et al, in press). It was also shown that they keep their tools safe in between foraging bouts (Auersperg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tool use innovations can be transmitted to naïve individuals by emulation learning and tool-using subjects are thereafter able to independently innovate tool manufacture (Auersperg et al, 2014). The birds respond flexibly, not only when choosing a tool, but also when making different tools from different materials depending on the problem at hand (Auersperg et al, 2016;Laumer et al, 2016Laumer et al, , 2017Habl & Auersperg, 2017;Auersperg et al, in press). It was also shown that they keep their tools safe in between foraging bouts (Auersperg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ecology of the Goffin's cockatoo remained largely unknown before we started our field research on this species (however, see Mioduszewska et al, submitted). Present knowledge from captivity suggests that the tool-related capacities of Goffin's cockatoos stem from domain general processing, which, in turn, could represent an adaptation to opportunistic extractive foraging (Laumer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We recently learned that Goffin’s cockatoos can innovatively manufacture the same (long stick-type) tool from different material sources [ 15 , 23 , 28 ]. Two subjects were able to fabric such tools from materials that required active shape-giving, such as cardboard [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…beak phenotypes might be retained if they are efficient for processing nonfavored resources, particularly if the favored resource is periodically limited (i.e., Liem's paradox;Liem 1980;Tebbich et al 2004). Furthermore, in addition to feeding and foraging, birds use their beaks for a plethora of other tasks, such as preening (Moyer et al 2002;Clayton et al 2005), vocal modulation (Podos 2001;Herrel et al 2009), thermoregulation (Tattersall et al 2009;van De Ven et al 2016) and water balance (Greenberg et al 2012), tool use (Weir et al 2002;Wimpenny et al 2009;Laumer et al 2017), nest construction (Hansell 2000), and as a display structure (Navarro et al 2009). This functional and behavioral flexibility implies that multiple selective pressures likely played important roles in shaping beak evolution.…”
mentioning
confidence: 99%